Observation and characterisation of macrophages in zebrafish liver. (May 2020) - Cheng, Delfine; Morsch, Marco; Shami, Gerald J.; Chung, Roger S.; Braet, Filip
Highlights: Liver macrophages play an important role in hepatic immunity. Mpeg1 zebrafish serves as a tool to study hepatic macrophages in zebrafish. Application of correlative light and electron microscopy enables the study of ultrastructure in zebrafish liver macrophages. Latex beads injection and peroxidase staining permits functional characterisation of zebrafish liver macrophages. Macrophages in the zebrafish liver show distinct differences compared to rodent liver macrophages. Abstract: Kupffer cells are liver-resident macrophages that play an important role in mediating immune-related functions in mammals and humans. They are well-known for their capacity to phagocytose large amounts of waste complexes, cell debris, microbial particles and even malignant cells. Location, appearance and functional aspects are important features used to identify these characteristic cells of the liver sinusoid. To-date, there is limited information on the occurrence of macrophages in zebrafish liver. Therefore, we aimed to characterise the ultrastructural and functional aspects of liver-associated macrophages in the zebrafish model by taking advantage of the latest advances in zebrafish genetics and multimodal correlative imaging. Herein, we report on the occurrence of macrophages within the zebrafish liver exhibiting conventional ultrastructural features ( e.g. presence of pseudopodia, extensive lysosomal apparatus, a phagolysosome and making up ∼3% of the liver volume). Intriguingly, these cells were not located within the sinusoidal vascular bed of hepatic tissue but instead resided between hepatocytes and lacked phagocytic function. While our results demonstrated the presence and structural similarities with liver macrophages from other experimental models, their functional characteristics were distinctly different from Kupffer cells that have been described in rodents and humans. These findings illustrate that the innate immune system of the zebrafish liver has some distinctly different characteristics compared to other animal experimental models. This conclusion underpins our call for future studies in order to have a better understanding of the physiological role of macrophages residing between the parenchymal cells of the zebrafish liver.